2013
DOI: 10.1155/2013/160582
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Adequately Iodized Salt at Household Level and Associated Factors in Gondar Town, Northwest Ethiopia

Abstract: Background. Iodine deficiency has serious effects on body growth and mental development. This study assessed availability of adequately iodized salt at household level and associated factors in Gondar town, northwest Ethiopia. Methods. Community based cross-sectional study was carried out among households in Gondar town during August 15–25, 2012. Multistage sampling technique was used. Data were collected using a pretested and structured questionnaire by a face-to-face interview technique. Bivariate and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
54
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 4 publications
14
54
8
Order By: Relevance
“…Participants' who did not expose salt to sunlight were about four times more likely to have adequately iodized salt as compared to their counterparts. This is consistent with the findings of the study conducted in northern Ethiopia on the presence of adequately iodized salt at home and factors affecting it [10]. A study from India shows loss of 31% of iodine from iodized salt because of exposure to sunlight [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants' who did not expose salt to sunlight were about four times more likely to have adequately iodized salt as compared to their counterparts. This is consistent with the findings of the study conducted in northern Ethiopia on the presence of adequately iodized salt at home and factors affecting it [10]. A study from India shows loss of 31% of iodine from iodized salt because of exposure to sunlight [28].…”
Section: Discussionsupporting
confidence: 91%
“…Out of the 440 households provided salt samples, adequately iodized salt was found only in 166 (37.7%) households using the titration method. The result of this study is higher than the findings observed in different parts of Ethiopia: Hawassa town 0% [18], Shebe town, south west Ethiopia 19% [19], Northern Ethiopia 25% [20], Gondar 29% [10], JigJiga town, Eastern Ethiopia 26.6% [21], and Laelay Maychew District, Northern Ethiopia 33% [22] of the households have access to iodized salt. The finding from the current study is also higher than the findings observed in Sudan 14.4% [9] and Sindh and Punjab provinces of Pakistan 15% [8].…”
Section: Discussioncontrasting
confidence: 65%
“…The finding is higher than stdudy done in Gondar North west Ethiopia in 2012, which was 28.9% (13), in Asosa 26.1% (14) and DHS 2011, which showed 23.2% of Urban HHs have access to iodized salt [10]. But low compared to other developing countries like Kenya, Uganda and Zimbabwe, which have successful HHs iodized salt coverage which is about 90% [13]. According to WHO, UNICEF and ICCIDD elimination of IDD is possible when the proportion of HHs using iodized salt reachs 90% [14], and Ethiopia also set target to reach 95% in 2014/2015 [15].…”
Section: Discussioncontrasting
confidence: 59%
“…The finding is higher than stdudy done in Gondar North west Ethiopia in 2012, which was 28.9% (13), in Asosa 26.1% (14) and DHS 2011, which showed 23.2% of Urban HHs have access to iodized salt [10]. But low compared to other developing countries like Kenya, Uganda and Zimbabwe, which have successful HHs iodized salt coverage which is about 90% [13].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation